2017
DOI: 10.1111/nep.12856
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to opportunistic chronic kidney disease screening by general practice nurses

Abstract: The findings of this study can be used to inform the development and evaluation of interventions that target opportunistic CKD screening in the GP setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 29 publications
2
37
1
3
Order By: Relevance
“…The major reason for the low referral uptake was GPs not initiating discussion on the risk assessment results. Also, the absence of an existing medical complaint might have enhanced participants’ reluctance to initiate discussion . Another contributing factor towards the low referral uptake could be the manner in which the results were communicated to the GP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major reason for the low referral uptake was GPs not initiating discussion on the risk assessment results. Also, the absence of an existing medical complaint might have enhanced participants’ reluctance to initiate discussion . Another contributing factor towards the low referral uptake could be the manner in which the results were communicated to the GP.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the absence of an existing medical complaint might have enhanced participants' reluctance to initiate discussion. 22 Another contributing factor towards the low referral uptake could be the manner in which the results were communicated to the GP. All GPs were sent a referral letter; however, it is possible that not all of them had the opportunity to read it before the patient visit.…”
Section: Discussionmentioning
confidence: 99%
“…
Box 4: Ensuring content directly addresses learning outcomes in CKD DETECT CKD DETECT was designed and developed to meet two key learning outcomes derived from the Kidney Health Australia ‐ Caring for Australians with Renal Insufficiency Guidelines (Johnson et al, ). A third outcome was developed from the findings of an elicitation study that identified the barriers and facilitators to opportunistic CKD screening by general practice nurses in an Australian primary care setting (Sinclair et al, ). This study concluded that many of the participants were familiar with risk criteria indicating who should be targeted for opportunistic screening and how screening should be undertaken.
…”
Section: Identify Learning Outcomes and Ensure Content Will Delivermentioning
confidence: 99%
“…The majority of e-learning research to date has focused on user satisfaction, knowledge improvement, or self-efficacy relating to clinical skills using subjective selfreported measures (Lahti et al, 2014). Few studies have examined the effectiveness of e-learning programs on health care professional (HCP) behavior using objectively administered evaluation criteria (Sinclair et al, 2016a); however, those that have considered effectiveness used Objective Structured Clinical Examination (OSCE) (Cantarero-Villanueva et al, 2012) or Objective Structured Assessment of Technical Skills (OSAT) (Pape-Koehler et al, 2013). These processes are impractical for evaluating clinical skills and behavior change in the asynchronous e-learning environment.…”
Section: Incorporate Elements To Enhance Retention Transfer and Behmentioning
confidence: 99%
“…Therefore, exploration of how best to support primary care providers (PC-P) to detect and manage CKD is needed. While several studies have explored factors impacting the management of CKD in the primary care setting [7][8][9][10], there is a need to identify common barriers and enablers in order to develop effective strategies to enhance CKD care. While a systematic review of barriers to CKD management in primary care has been published [11], this study did not explore enabling factors.…”
Section: Introductionmentioning
confidence: 99%